Moringa oleifera Leaf Extract Promotes Healing of Infected Wounds in Diabetic Rats: Evidence of Antimicrobial, Antioxidant and Proliferative Properties - Abdullah A. Al-Ghanayem; Mohammed Sanad Alhussaini; Mohammed Asad; Babu Joseph (MDPI AG, 2022)
Moringa oleifera is known to possess wound healing activity. The present study evaluated the healing properties of methanolic extract of M. oleifera leaves in excision wounds infected with methicillin-resistant Staphylococcus aureus (MRSA) or P. aeruginosa in diabetic rats. An in vitro study was also carried out to determine the gene expression of VEGF and TGF-β1. Preliminary phytochemical and GC-MS analyses were carried out to determine different chemical constituents present in the extract. M. oleifera was applied locally as an ointment at two different concentrations. Wound contraction, period of epithelization, antioxidant enzyme activities and histological changes were determined. For the gene expression study, HaCaT cell lines were used. The formulation of M. oleifera extract improved wound contraction and decreased the period of epithelization, which was associated with an increase in antioxidant enzyme activities, epithelization, capillary density and collagen formation in MRSA-infected diabetic rats. However, this effect was reduced in diabetic animals infected with P. aeruginosa. An increase in the expression of VEGF and TGF-β1 was observed in HaCaT cell lines. M. oleifera extract promotes the healing of infected wounds in MRSA-infected diabetic rats but is less effective in the healing of wounds infected with P. aeruginosa in diabetic rats.